2019
DOI: 10.1111/mpp.12881
|View full text |Cite
|
Sign up to set email alerts
|

The fungal subtilase AsES elicits a PTI‐like defence response in Arabidopsis thaliana plants independently of its enzymatic activity

Abstract: Summary Acremonium strictum elicitor subtilisin (AsES) is a 34‐kDa serine‐protease secreted by the strawberry fungal pathogen A. strictum. On AsES perception, a set of defence reactions is induced, both locally and systemically, in a wide variety of plant species and against pathogens of alternative lifestyles. However, it is not clear whether AsES proteolytic activity is required for triggering a defence response or if the protein itself acts as an elicitor. To investigate the necessity of the protease activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 71 publications
(94 reference statements)
1
6
0
Order By: Relevance
“…Due to the large number of duplications, losses, and functional diversifications in the evolution of subtilisin superfamily, there are large differences in subtilisin phylogeny ( Li et al, 2017 ). Subtilisin has a certain degree of conservation across different classes of microbes to general microbial fitness ( Caro et al, 2020 ), while conserved functional residues are critically important for protein function. For example, specific residues of AtZAR1, a canonical CC-type NLR protein from Arabidopsis , are required for its immune function against Pseudomonas syringae pv.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the large number of duplications, losses, and functional diversifications in the evolution of subtilisin superfamily, there are large differences in subtilisin phylogeny ( Li et al, 2017 ). Subtilisin has a certain degree of conservation across different classes of microbes to general microbial fitness ( Caro et al, 2020 ), while conserved functional residues are critically important for protein function. For example, specific residues of AtZAR1, a canonical CC-type NLR protein from Arabidopsis , are required for its immune function against Pseudomonas syringae pv.…”
Section: Introductionmentioning
confidence: 99%
“…tomato DC3000 ( Baudin et al, 2017 ). In search of whether the proteolytic activity of AsES, a subtilisin from Acremonium strictum , is required to trigger the defence response, its mutants at the active site (S226A) have confirmed that AsES induced the plant defense, and that enzymatic and eliciting activities were not associated ( Caro et al, 2020 ). However, key residues of subtilisin triggering defence responses to pathogens remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis thaliana is an important model host for studying plant–pathogen interactions due to the ease with which it can be studied by genetic and mutational analysis. Isolation of pathogens that infect both crops and Arabidopsis has greatly facilitated the understanding of plant defence mechanisms (Caro et al, 2020). Transferring genes involved in innate immunity from model plants to crops could also be a promising alternative for genetic improvement, and several studies have already proved its feasibility (Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis thaliana is an important model host for studying plant-pathogen interactions due to the ease with which it can be studied by genetic and mutational analysis. Isolation of pathogens that infect both crops and Arabidopsis has greatly facilitated the understanding of plant defence mechanisms (Caro et al, 2020).…”
mentioning
confidence: 99%
“…Our research group has identified and characterized a defence elicitor protein called Acremonium strictum Elicitor Subtilisin (AsES), which was isolated from the opportunist fungus Acremonium strictum (Chalfoun et al 2013) (patent AR/10.03.11/ARA P110100854). It was reported that AsES induces a systemic defence response in different strawberry cultivars and in Arabidopsis thaliana by activating a broad spectrum of biochemical and molecular processes associated with the plant defence response (Chalfoun et al 2013; Hael‐Conrad et al 2015; Caro et al 2019). Besides its protective effects in vegetative stages, Perato et al (2018) also reported that AsES induces ripening and enhances protection against naturally produced disease in avocado fruit.…”
Section: Introductionmentioning
confidence: 99%